1978
DOI: 10.1007/bf02304367
|View full text |Cite
|
Sign up to set email alerts
|

Some results of observations of thermal cracking in the concrete in the Ust-Ilim dam

Abstract: Between 1969 and 1976,'1652 cracks were found in the Ust-Ilim dam concrete. The cracks were recorded in 1042 blocks of the structure (Table I). The overwhelming majority of cracks (87-88%) were surface or shallow (less than 1.0-m depth of propagation into the blocks) and 12-13% of the cracks were through or deep. Cracks splitting the blocks apart were considered through cracks, cracks penetrating to a depth of more than 1.0-1.5 m were considered deep; 79 cracks in the first column of the dam proved to be perco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1979
1979
1979
1979

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Field observations at the Ust-Ilim Dam showed that the greatest crack formatlon was associated with the early removal of block forms during the winter [7] and with the v~gorous cooling of plant sections under construction with hollow pressurized condus open to the freezing air [8].…”
Section: [4]mentioning
confidence: 99%
“…Field observations at the Ust-Ilim Dam showed that the greatest crack formatlon was associated with the early removal of block forms during the winter [7] and with the v~gorous cooling of plant sections under construction with hollow pressurized condus open to the freezing air [8].…”
Section: [4]mentioning
confidence: 99%